Advances Of AI And ML Technologies For Enhanced Cancer Prediction: An Exploratory Examination (Journal of Namibian Studies : History Politics Culture, 2023)
Actually, when it comes to cancer prediction, AI and ML have proven to be more accurate than human doctors. Patients with a wide range of disorders, not just cancer, can benefit from these technologies in terms of diagnosis, prognosis, and general health. This highlights the critical need to develop new patient-beneficial programs and to improve current AI and ML approaches. This article delves into the field of cancer prediction using AI and ML algorithms, exploring its current applications, limitations, and prospective future usage. Clinical applications of AI and ML in cancer diagnosis and therapy are the wave of the future when it comes to medical advice. Medical practitioners will be able to more rapidly develop unique treatment plans for each patient with the use of these apps.